Pemberdayaan Masyarakat : Kelompok Sadar Wisata (Pokdarwis) sebagai Motor Penggerak Pariwisata di Daerah Tujuan Wisata (DTW) Guci Kabupaten Tega - Trisnoasih, Triana Mukti; ., Turtiantoro (Journal of Politic and Government Studies, 2019)
Tourism conscious Group have a fungtion as a driving force for tourism, so empowerment is needed to increase the strength or power of the community. Pokdarwis Guci has not carried out the role as itu should be. So this study aims to describe community empowerment in the tourism sector, to know the role of Pokdarwis so far, and to analyze the factors of obstacles ang opportunities for community empowerment and the movement of Pokdarwis Guci. This study uses qualitative methods with data collection techniques in the form of observations, in-depth interviews and documents. Then analyzed using data source triangulation. The results of the study explained that empowerment was carried out by various parties. For tourism, especially in strengthening human resources, strengthening institutions, from the government to conduct networking and guidance for traders and provide other support. Pokdarwis experienced complexity in its existence, social capital that was not strong became the main factor so that the current Pokdarwis trip to death did not work as it should. Barries to empowerment and the Pokdarwis movement, namely weak Pokdarwis institutions, backwardness of the community of jars, lack of community participation, orientation of the old paradigm of empowerment, attention from the village government is not optimal, and education to the community in lacking. And there are opportunities namely optimism for Pokarwis, development of DTW Guci, development plans for Guci village.Key Words : Community Empowerment, Pokdarwis, DTW Guci